O stylotwórczej funkcji formacji rzeczownikowych z przyrostkiem -ość w Psałterzu Dawidowym Mikołaja Reja (1543) - Kowalska, Danuta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The aim of the analyses presented in this article is to determine the stylistic conditions associated with the distribution of noun formations with the suffix -ość in Mikołaj Rej’s Psałterz Dawidów (David’s Psalter) from 1543. The conducted observations reveal that Rej employed such abstract nouns to shape the stylistic and linguistic layer of his prose translation. In line with general 16th-century tendencies, Rej used these formations not only as means of artistic expression, but also to construct the semantic level of the Psalter’s text. This included avoiding concrete expressions in favor of general, timeless, and universal terms – an approach that softened the harshness of the psalmist’s realist narrative. He further utilized nomina essendi as markers of hyperbole and superlative expression, aiming to evoke emotional responses and enhance the expressiveness of the utterance. These derivatives also served a rhythmic function in the prose paraphrase, imitating external features of Hebrew poetry. This latter function is particularly noticeable: the translator not only grouped morphologically similar nouns in close proximity but also paid attention to their syntactic placement to maximize the text’s sound qualities. These auditory effects were further reinforced by the inflectional endings shared by the analyzed derivatives. Rej’s individual preferences regarding noun formations demonstrate his refined stylistic sensitivity, presenting him as an artist who consciously shaped the stylistic dimension of the translated text by skillfully exploiting the derivational and even inflectional potential (e.g., his fondness for plural forms of abstract nouns) of 16th-century Polish.